PROJECTS IN CZECH SCHOOLS - DOMISCHOVA, Ivona (Trends in education, 2010)
This contribution analyses the situation of project classes at the Czech schools from the point of view of practical realisation of different projects. It analyses the preparation of students who study "German language with focus on education for new structured study" at Pedagogical faculty Palacky University. At Pedagogical faculty a new course "Project class" will be opened.
Keywords: project teaching; project method; education; student; branch of study; studies; foreign countries.